18th century Portuguese tiles: characterization and reproduction study of Ca-rich biscuits - Morais Pereira, S. (2016)
Majolica tiles from the 17th-18th centuries make up one of the most important art heritages of Portugal. Their characterization and gains in knowledge through their reproduction are important to obtain information about their production methods, raw materials used, origin attribution and to contribute to studies in conservation and development of treatments. A group of Lisbon tiles from the late 17th to 18th centuries has been previously characterized and the biscuits now tentatively reproduced. Special attention was given to the effect of firing temperature and Ca compounds content on the final replica properties such as water absorption, porosity, water and thermal expansibilities, mechanical strength, chemical composition and mineralogy. Correlation models between the Ca compounds content and firing temperature were obtained for the previous properties. Replicas similar on those properties considered relevant were obtained that can be used in studies in conservation and in interventions.